Experimental Investigation of Natural Plant Extracts as A Green Corrosion Inhibitor in Steel - Akrom, Muhamad (Journal of Renewable Energy and Mechanics, 2022)
Natural plant extracts show excellent performance in inhibiting steel corrosion. Steel has a relatively weak resistance to corrosion when in a corrosive environment. The use of natural plant extracts as green corrosion inhibitors is able to provide good performance with high inhibition efficiency. Experimental methods such as gravimetric analysis, potentiodynamic polarization, and electrochemical impedance spectroscopy are commonly used to investigate corrosion inhibition based on corrosion activity. A comparative literature review of this work is important for the development and utilization of green inhibitors. Experimental studies still do not clearly reveal the mechanism of adsorption and inhibition of molecular inhibitors at the atomic level. For this reason, future developments are very important to study theoretically at the atomic level of the main components of natural plant extracts as corrosion inhibitors, so that it is hoped that there will be a clear and systematic understanding of the mechanism of corrosion inhibition in steel.